2019
DOI: 10.1007/s40262-018-0727-5
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Pharmacokinetics Throughout Life: Results from a Pooled Population Analysis and Evaluation of Current Dosing Recommendations

Abstract: Background and Objectives Uncertainty exists regarding the optimal dosing regimen for vancomycin in different patient populations, leading to a plethora of subgroup-specific pharmacokinetic models and derived dosing regimens. We aimed to investigate whether a single model for vancomycin could be developed based on a broad dataset covering the extremes of patient characteristics. Furthermore, as a benchmark for current dosing recommendations, we evaluated and optimised the expected vancomycin exposure throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 48 publications
2
77
2
Order By: Relevance
“…Guidelines for dose individualization in routine clinical practice are often based on local experience or expert opinion and it is unclear to what extent such guidelines actually achieve target concentrations or exposure. A recent study 8 found that consensus guidelines produced by the US Food and Drug Administration (FDA) and also the Summary of Product Characteristics for vancomycin performed poorly when tested using a large population of patients. Furthermore, even when guidelines are available, they may not be in a form that can be implemented effectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Guidelines for dose individualization in routine clinical practice are often based on local experience or expert opinion and it is unclear to what extent such guidelines actually achieve target concentrations or exposure. A recent study 8 found that consensus guidelines produced by the US Food and Drug Administration (FDA) and also the Summary of Product Characteristics for vancomycin performed poorly when tested using a large population of patients. Furthermore, even when guidelines are available, they may not be in a form that can be implemented effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even when guidelines are available, they may not be in a form that can be implemented effectively. For example, although Colin et al 8 . found that modified versions of the FDA and Summary of Product Characteristics guidelines were more likely to achieve target exposure, the resulting dose amounts were impractical for routine clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations